PENGGUNAAN MEDIA ALTERNATIVE (DIAPERS) TERHADAP PERTUMBUHAN DAN PRODUKSI TANAMAN CABAI - Safrizal, Safrizal; Nazimah, Nazimah; Resssi, Rina (Faculty of Agriculture, Universitas Malikussaleh, 2018)
Red chili is a major vegetable both in Indonesia and abroad due to its benefits to the needs of nutrition and health through cooking spices. Utilization of home garden yard is an effective way to cultivate pepper plants. On the other hand, every household produces household waste which is difficult to decompose for instance diapers, so that it can cause environmental pollution in long-term. This study was conducted to investigate the role of planting media such as diapers of on chili growth. The results showed that the use of diapers of diapers as planting media gave no significant different to plant height at 1, 4, 7, 10, 13 and 16 week after application. It also did not increase the number of leaves at the age of 1, 7, 10, 13 and 16 week after application. There were no changes in leaf length at ages 1, 4, 7, 10 and 16 week after application. It also happened to also its leaf width at ages 1, 4, 7, 10, 13 and 16 week after application and number of branches at ages 1, 4, 7, 13 and 16 week after aplication. However, it showed a significant different to the number of leaves at age 4 week after planting and its leaf length at age 13 week after planting. The interaction of using diapers as planting media gave significantly different response to root number, root length, wet root weight and plant canopy, and dry weight roots and plant canopy.